Evaluación de la respuesta del taxo (passiflora tarminiana l.) a la aplicación de dos bioreguladores en dos etapas fenológicas de la producción con dos porcentajes de raleo manual para mejorar la calidad de la fruta, en Isinche Grande-Pujili, Cotopaxi - Reyes Reinoso, José Ricardo (2014)
The aim of this research was to evaluate the response of taxo (Passiflora tarminiana. L.) to the application of two bioregulators in two phenological stages of production with two percentages of manual sparse to improve the fruit quality. The place was in the Cotopaxi province, Pujilí canton, Pujilí parish, Isinche Grande neighborhood; in the Mr. José Reyes Rivera’s own. It was researched three factors in study. The first, Agrostemin bioregulators, Kelpak and control, the second; a phenological stage of application at the beginning of the flowering and beginning of fructification and the third factor was manual sparse to 20% and 40%. From the combination of factors in study, it was obtained 12 treatments applied in a designing of plot of land divided twice with a 3 x 2 x 2 factorial. The interpretation of the results was carried out through the analysis of variance (ADEVA), 5% Tukey's test at 5% and the minimum and significant test at 5% to the variation sources that were significant in ADEVA 1%. For the profitability calculation, it was done the benefit/cost process….